Estimation of withdrawal interval recommendations following administration of fenbendazole medicated feed to ring-necked pheasants (Phasianus colchicus) - Carreño Gútiez, Marta; Mercer, Melissa A.; Martínez-López, Beatriz; Griffith, Ronald W.; Wetzlich, Scott; Tell, Lisa A. (Frontiers in Veterinary Science, 2024)
Introduction Prescribing fenbendazole medicated feed for pheasants in the USA is considered extra-label drug use under CPG Sec 615.115, and a safe estimated withdrawal interval (WDI) must be applied following administration to this minor food-producing species. This study sought to determine the pharmacokinetic and residue depletion profile for fenbendazole and its major metabolites to estimate a WDI for pheasants following fenbendazole administration as an oral medicated feed. Method Pheasants (n = 32) were administered fenbendazole as an oral medicated feed (100 ppm) for 7 days. Fenbendazole, fenbendazole sulfoxide, and fenbendazole sulfone (FBZ-SO2) in liver and muscle samples were analyzed using HPLC-UV. Tissue WDIs were estimated using FDA, European Medicines Agency (EMA), and half-life multiplication methods for US poultry tolerances, EMA maximum residue limits, and the analytical limit of detection (LOD; 0.004 ppm). Terminal tissue elimination half-lives (T1/2) were estimated by non-compartmental analysis using a naïve pooled data approach. Results The tissue T1/2 was 14.4 h for liver, 13.2 h for thigh muscle, and 14.1 h for pectoral muscle. The maximum estimated withdrawal interval was 153 h (7 days) for FBZ-SO2 in pectoral muscle using the FDA tolerance method (95% confidence interval for the 99th percentile of the population), and the LOD as the residue limit. Discussion The results from this study support the use of FBZ-SO2 as the marker residue in the liver of pheasants and the provision of evidence based WDIs following the extra-label administration of fenbendazole medicated feed (100 ppm) for 7 days.